Pengaruh Perdagangan Karbon Terhadap Kondisi Ekologi di Indonesia - Samasta, Nadia Azhar (Jurnal Biologi, 2023)
Climate change and ecological degradation are two global phenomena that are of serious concern in Indonesia. To overcome these problems, carbon trading is one of the strategies used in an effort to reduce greenhouse gas emissions. The purpose of this study is to analyze the effect of carbon trading on ecological conditions in Indonesia. The research method used is a literature review model with descriptive qualitative data analysis techniques. The results showed that carbon trading has a positive influence in maintaining ecological sustainability in Indonesia through reducing greenhouse gas emissions and implementing sustainable practices. In conclusion, carbon trading plays an important role in influencing ecological conditions in Indonesia by making a significant contribution in reducing greenhouse gas emissions and improving sustainability practices.